Intraperitoneal administration of choline increases serum glucose in rat: Involvement of the sympathoadrenal system - (:unkn) unknown (GEORG THIEME VERLAG KG, 2002)
Intraperitoneal injection of choline (40, 80 or 120 mg/kg) produced a dose-dependent increase in serum glucose and choline levels in rats. The increases in serum glucose and choline were associated with an increase of serum insulin as well as plasma levels of epinephrine and norepinephrine. The increases in serum glucose and plasma catecholamine concentrations induced by choline (120 mg/kg) were blocked by pretreatment with the ganglionic nicotinic receptor antagonist hexamethonium (15 mg/kg), but were not affected by pretreatment with atropine (5 mg/kg). The choline-induced rise in serum insulin was blocked by pretreatment with atropine and with hexamethonium each. The increase in serum glucose evoked by choline (120 mg/kg) was blocked by alpha-adrenoceptor blockade and bilateral adrenalectomy each. Blockade of beta-adrenoceptor by propranolol or chemical sympathectomy by 6-hydroxydopamine failed to alter the hyperglycemic response to choline. These results show that choline, a precursor of the neurotransmitter acetylcholine, increases serum glucose and insulin levels. The effect of choline on serum insulin is mediated by both muscarinic and nicotinic acetylcholine receptors, whereas the effect of choline on serum glucose is mediated solely by nicotinic receptors. The stimulation of adrenal medullary catecholamine release and subsequent activation of alpha-adrenoceptors apparently mediates the hyperglycemic effect of choline.
Keywords: precursor; hyperglycemia; insulin; Catecholamines; alpha-adrenoceptor; adrenal medulla; sympathetic system; ACETYLCHOLINE-RELEASE; TYROSINE-HYDROXYLASE; ALZHEIMERS-DISEASE; INJECTED CHOLINE; CDP-CHOLINE; INSULIN; MEMORY; CITICOLINE; SECRETION; ENHANCEMENT